Comparative proteomics of bark and xylem provides insights into age-dependent corticular photosynthesis in Eucalyptus grandis - da Silva, Felipe Alexsander Rodrigues; de Lima, Daniele Cristine; Labate, Mônica T. Veneziano; Budzinski, Ilara Gabriela Frasson; Cataldi, Thais Regiani; Labate, Carlos Alberto (Frontiers in Plant Science, 2026)
IntroductionEucalyptus species are globally important for forestry due to rapid growth, adaptability, high biomass production, and contribution to carbon sequestration by storing atmospheric CO2 as biomass. However, the metabolic mechanisms sustaining growth under hypoxic conditions within woody vascular tissues remain unclear. Here, we investigate whether corticular photosynthesis helps sustain stem energy metabolism across two developmental stages in vascular tissues of Eucalyptus grandis.MethodsWe analyzed bark and xylem from 4- and 12-year-old clonal Eucalyptus grandis plants. Chloroplast abundance in bark was quantified by fluorescence microscopy, and both tissues were profiled by shotgun proteomics.ResultsChloroplasts were more abundant in younger bark and were not detected in xylem. A total of 3,113 non-redundant proteins were identified, and enrichment analysis indicated a consistent hypoxic response across tissues and ages, alongside age-specific metabolic processes. Proteoform abundance patterns implicated glycolysis, the tricarboxylic acid cycle, and fermentation pathways. Alcohol dehydrogenase and aldehyde dehydrogenase proteoforms showed differential abundance in xylem and younger bark, consistent with greater emphasis on fermentative metabolism in hypoxia-prone vascular tissues. Younger bark also exhibited higher abundance of Calvin–Benson cycle proteins, together with higher chloroplast numbers than older bark and xylem, indicating higher potential for local carbon fixation and oxygen availability in juvenile stems.DiscussionThese findings underscore adaptive metabolic strategies of eucalyptus stems, refine current models of corticular photosynthesis and stem energy metabolism in fast-growing trees, and provide a molecular framework for future physiological studies in eucalyptus and other woody species.